A PEX5 missense allele preferentially disrupts PTS1 cargo import into Arabidopsis peroxisomes. (20th March 2019) - Patel, Khushali J.; Kao, Yun‐Ting; Llinas, Roxanna J.; Bartel, Bonnie
Abstract: The sorting of eukaryotic proteins to various organellar destinations requires receptors that recognize cargo protein targeting signals and facilitate transport into the organelle. One such receptor is the peroxin PEX5, which recruits cytosolic cargo carrying a peroxisome‐targeting signal (PTS) type 1 (PTS1) for delivery into the peroxisomal lumen (matrix). In plants and mammals, PEX5 is also indirectly required for peroxisomal import of proteins carrying a PTS2 signal because PEX5 binds the PTS2 receptor, bringing the associated PTS2 cargo to the peroxisome along with PTS1 cargo. Despite PEX5 being the PTS1 cargo receptor, previously identified Arabidopsis pex5 mutants display either impairment of both PTS1 and PTS2 import or defects only in PTS2 import. Here, we report the first Arabidopsis pex5 mutant with an exclusive PTS1 import defect. In addition to markedly diminished GFP‐PTS1 import and decreased pex5‐2 protein accumulation, this pex5‐2 mutant shows typical peroxisome‐related defects, including inefficient β‐oxidation and reduced growth. Growth at reduced or elevated temperatures ameliorated or exacerbated pex5‐2 peroxisome‐related defects, respectively, without markedly changing pex5‐2 protein levels. In contrast to the diminished PTS1 import, PTS2 processing was only slightly impaired and PTS2‐GFP import appeared normal in pex5‐2 . This finding suggests that even minor peroxisomal localization of the PTS1 protein DEG15, the PTS2‐processing protease, is sufficient to maintain robust PTS2 processing.